De Shirley à Villette : comment Jane Eyre peut-elle vieillir ? - Bernadette Bertrandias (Cahiers Victoriens et Edouardiens)
While Jane Eyre obliterates the process of getting old, not so for Charlotte’s two subsequent novels which introduce singular characters whose connection with the heroine suggests that ageing is now part of the issue of self development with which her writings are concerned. In Shirley, the old maids are monitory figures, but in Villette, Miss Marchmont, on the one hand (whose fate can be read as the alternative of Jane Eyre’s), and the monstrous Malevola, on the other hand, frame Lucy Snowe’s progress in life in a paradoxical structure of closeness/strangeness regarding the process of ageing. This article attempts to read the function of those figures as part of the problematic maturation of the woman subject, as uneasy with the codes of the Bildungsroman as such, as with those of patriarchy at large. For if Malevola illustrates the ultimate degradation of feminine stereotypes, she also embodies the parodic obverse of the woman writer’s manipulative power, and as such maybe the last mirror in which Brontë contemplates herself, with the issue of autonomy and self-fulfilment dramatically unresolved.